Water gas shift reaction catalyst
Through the catalyst composition of zinc-aluminum spinel phase and zinc oxide, the reduction problem of existing catalysts when operating at low steam to gas ratio is solved, and a chromium-free and iron-free water-gas transformation catalyst is realized at high temperatures. Wide range of adaptability and higher activity, avoiding environmental pollution.
Patent Information
- Application Number
- CN202380042611.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-09
- Filing Date
- 2023-05-23
- Publication Date
- 2025-01-03
AI Technical Summary
The iron-chromium and copper-zinc metal combinations commonly used in existing water-gas transformation reaction catalysts have health and environmental problems, and they are easily reduced to produce hydrocarbon by-products when operating at low steam to gas ratio, making it difficult to within a wider range. Effective use.
Using a catalyst composition based on zinc-aluminum spinel phase and zinc oxide, a high-temperature water gas transformation catalyst without chromium is prepared by providing a precipitation and calcination of a precursor aqueous solution containing zinc ions and aluminum ions. The zinc atoms in the catalyst are prepared and calcined. The molar ratio of aluminum atoms is at least 1:1, contains a small amount of crystalline Al2O3 phase, and exhibits good activity and stability at high temperatures.
A chromium-free and iron-free water-gas transformation catalyst is achieved at high temperatures, with a wider range of steam-to-gas ratios and higher catalytic activity, avoiding the environmental impact of chromium and iron, while in the presence of sulfur It also maintains long-term efficient performance.
Smart Images

Figure CN119255864A_ABST
Abstract
Description
Public background Public domain
[0002] The present disclosure relates generally to water-gas shift reaction catalyst materials. More specifically, the present disclosure relates to spinel-containing catalysts useful in high temperature water-gas shift reactions, to methods of making such catalysts, and to methods of forming hydrogen with such catalysts. Technical Background
[0003] The water gas shift reaction is a well-known reaction by which hydrogen is formed from water vapor and carbon monoxide. Many important chemical reactions require large amounts of hydrogen. Since the 1940s, the water gas shift reaction has represented an important step in the industrial production of hydrogen. For example, industrial-scale water gas shift reactions are used to increase the production of hydrogen for refinery hydrogenation processes and for the production of commodity chemicals such as ammonia, methanol, and alternative hydrocarbon fuels.
[0004] Conventionally, catalysts used for industrial-scale water-gas shift reactions include either an iron-chromium metal combination or a copper-zinc metal combination. Iron-chromium oxide catalysts are typically used in high temperature shift (HTS) converters, which typically have a reactor inlet temperature of about 300°C to about 380°C. Conventional HTS converters use iron-based catalysts. Typically, catalysts containing 8%-12% Cr are used. 2 O 3 The conventional catalyst is supplied in the form of pellets with a small amount of copper as an activity and selectivity enhancer.
[0005] However, chromium can be toxic and carcinogenic and is therefore highly undesirable for use on an industrial scale due to health and environmental issues. In addition, iron-containing HTS catalysts can only be used over a limited range of steam to gas ratios (S / G; i.e., H 2 O and H 2 , N 2 , CO 2 This is because at low S / G the catalyst is reduced to iron carbides which produce hydrocarbon by-products.
[0006] Therefore, there remains a need for water-gas shift reaction catalysts that can be prepared without chromium and optionally without iron without significantly affecting performance. In addition, there is a need for water-gas shift reaction catalysts that can operate over a wider S / G range than conventional catalysts can tolerate. Overview
[0008] The inventors of the present application have determined that a catalyst based on a zinc-aluminum spinel phase with a large amount of ZnO phase can provide high temperature activity and stability at low cost and without the negative environmental impact of using large amounts of chromium. Therefore, one aspect of the present disclosure provides a high temperature water-gas shift catalyst composition comprising:
[0009] A ZnO phase, present in the composition in an amount of 5-70 wt %;
[0010] a zinc-aluminum spinel phase, present in the composition in an amount of 30-95% by weight;
[0011] The molar ratio of Zn atoms to Al atoms in the catalyst composition is at least 1:1.
[0012] In various embodiments, the catalyst composition further comprises little to no crystalline Al 2 O 3 Mutually.
[0013] Another aspect of the present disclosure provides a method for preparing the high temperature water-gas shift catalyst composition described herein. The method comprises:
[0014] providing a precursor aqueous solution comprising zinc ions and aluminum ions;
[0015] A solid catalyst precursor comprising salts of zinc, aluminum and, if present, promoter ions is precipitated from the aqueous precursor solution; and then
[0016] The solid catalyst precursor is calcined to provide a catalyst composition.
[0017] Another aspect of the present disclosure provides a method of performing a water gas shift reaction comprising contacting a feed comprising water and carbon monoxide with a water gas shift catalyst composition described herein to form hydrogen and carbon dioxide. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 is a graph of X-ray diffraction (XRD) patterns of certain materials described herein.
[0019] Figure 2 is a graph of X-ray diffraction (XRD) patterns of certain materials described herein. Detailed Description
[0021] The present disclosure relates to a water-gas shift catalyst composition comprising at least zinc, aluminum and oxygen, having a large amount of zinc-aluminum spinel and a large amount of zinc oxide. The present disclosure shows that such a catalyst, which may advantageously be substantially free of chromium, can exhibit good activity in the water-gas shift reaction, particularly the high temperature water-gas shift reaction.
[0022] Accordingly, one aspect of the present disclosure is a high temperature water-gas shift catalyst composition comprising:
[0023] a zinc-aluminum spinel phase, present in the composition in an amount of 30-95% by weight; and
[0024] A ZnO phase, present in the composition in an amount of 5-70 wt %;
[0025] The molar ratio of Zn atoms to Al atoms in the catalyst composition is at least 1:1.
[0026] For purposes of this disclosure, the amount of phases is determined using X-ray diffraction with Littlefield refinement. The amount of phase is reported as a fraction of crystals.
[0027] As noted above, the zinc-aluminum spinel phase is present in the composition of this aspect in an amount of 30-95% by weight. In various embodiments described herein in addition, the zinc-aluminum spinel phase is present in the composition in an amount of 30-90% by weight, for example, 30-85% by weight, or 30-80% by weight, or 30-75% by weight or 30-70% by weight. In various embodiments described herein in addition, the zinc-aluminum spinel phase is present in the composition in an amount of 40-95% by weight, for example, 40-90% by weight, or 40-85% by weight, or 40-80% by weight, or 40-75% by weight or 40-70% by weight. In various embodiments described herein in addition, the zinc-aluminum spinel phase is present in the composition in an amount of 45-95% by weight, for example, 45-90% by weight, or 45-85% by weight, or 45-80% by weight, or 45-75% by weight or 45-70% by weight. In various embodiments otherwise described herein, the zinc-aluminum spinel phase is present in the composition in an amount ranging from 50-95 wt %, e.g., 50-90 wt %, or 50-85 wt %, or 50-80 wt %, or 50-75 wt % or 50-70 wt %.
[0028] The zinc-aluminum spinel phase can have various grain sizes. In various embodiments, the zinc-aluminum spinel phase of the composition described herein has an average grain size in the range of 1-100 nm. For example, in various embodiments, the zinc-aluminum spinel phase has an average grain size of 1-75 nm, or 1-50 nm, or 1-30 nm, or 5-100 nm, or 5-75 nm, or 5-50 nm, or 5-30 nm, or 10-100 nm, or 10-75 nm, or 10-50 nm, or 25-100 nm, or 25-75 nm, or 50-100 nm. Smaller grain sizes of the zinc-aluminum spinel phase can be associated with higher surface areas and can provide higher catalytic activity.
[0029] As noted above, ZnO is present in the composition of this aspect in an amount in the range of 5-70 wt %. The amount of ZnO in the catalyst composition of the present disclosure can be changed within this range. For example, in various embodiments described in addition herein, ZnO is present in an amount in the range of 5-60 wt %, for example, 5-50 wt % or 5-40 wt %. In various embodiments described in addition herein, ZnO is present in the composition in an amount of 25-75 wt %, for example, 5-70 wt %, for example, 15-60 wt %, or 15-50 wt %, or 15-40 wt %. In various embodiments described in addition herein, ZnO is present in the composition in an amount of 25-70 wt %, for example, 25-60 wt %, or 25-50 wt % or 25-40 wt %. In various embodiments described in addition herein, ZnO is present in the composition in an amount of 30-70 wt %, for example, 30-60 wt %, or 30-55 wt % or 30-50 wt %. In various embodiments otherwise described herein, the ZnO phase is present in the composition at 35-70 wt%, eg, 35-65 wt%, or 35-60 wt% or 35-65 wt%.
[0030] In various embodiments described herein in addition, the ZnO phase in the composition described herein in addition has an average grain size in the range of 1-100 nm. For example, in various embodiments the ZnO phase has an average grain size of 1-75 nm, or 1-50 nm, or 1-30 nm, or 5-100 nm, or 5-75 nm, or 5-50 nm, or 5-30 nm, or 10-100 nm, or 10-75 nm, or 10-50 nm, or 25-100 nm, or 25-75 nm or 50-100 nm. Having a higher surface area can provide a larger total catalytic surface area, and therefore can result in generally higher catalytic activity.
[0031] Since zinc-aluminum spinel itself has an idealized ZnAl 2 O 4, it is therefore desirable to select a ratio of zinc to aluminum that, along with the other elemental components, provides the desired amount of spinel structure. Thus, in this aspect of the present disclosure, the molar ratio of Zn atoms to Al atoms in the catalyst composition is at least 1:1. In order to provide a large amount of ZnO, as described herein, it is desirable to provide zinc in a molar amount that exceeds the amount necessary to form spinel. For example, in various embodiments described herein, the molar ratio of Zn atoms to Al atoms is at least 1.1:1, e.g., at least 1.15:1 or at least 1.2:1. In various embodiments, the molar ratio of Zn atoms to Al atoms is at least 1.25:1, e.g., at least 1.3:1 or at least 1.35:1. In various embodiments, the molar ratio of Zn atoms to Al atoms is at least 1.4:1, e.g., 1.45:1 or 1.5:1. Of course, in order to provide the desired amount of spinel, it is desirable that the ratio is not too high. In various embodiments, the molar ratio of Zn atoms to Al atoms in the composition is no greater than 2.5: 1, e.g., no greater than 2.25: 1, or no greater than 2: 1, or no greater than 1.75: 1. In various embodiments, the molar ratio of Zn atoms to Al atoms in the composition is in the range of 1: 1-2.5: 1, e.g., 1: 1-2.25: 1 or 1: 1-2: 1 or 1: 1-1.75: 1. In various embodiments, the molar ratio of Zn atoms to Al atoms is between 1:1 and 2.5:1, e.g., 1:1 to 2.25:1, or 1:1 to 2:1, or 1:1 to 1.75:1, or 1.15:1 to 2.5:1, or 1.15:1 to 2.25:1, or 1.15:1 to 2:1, or 1.15:1 to 1.75:1, or 1.25:1 to 2.5:1, or 1.25:1 to 2.5:1. .25:1, or 1.25:1-2:1, or 1.25:1-1.75:1, or 1.35:1-2.5:1, or 1.35:1-2.25:1, or 1.35:1-2:1, or 1.35:1-1.75:1, or 1.45:1-2.5:1, or 1.45:1-2.25:1, or 1.45:1-2:1 or 1.45:1-1.75:1. The inventors of the present application have determined that various such Zn / Al ratios can provide a ZnAl containing not only ZnAl 2 O 4 Spinel phase, also contains a catalyst composition of a large amount of ZnO phase. The inventors of the present application have found that excess ZnO can be beneficial to the long-term performance of the catalyst composition. In commercial water-gas shift reactors, the feed often contains sulfur at ppb levels. It is well known that sulfur irreversibly deactivates water-gas shift catalysts. The inventors have found that the catalyst formulations described herein with an increased Zn / Al ratio can not only have a higher initial activity, but also have a higher activity after exposure to sulfur under operating conditions compared to catalysts with lower Zn / Al ratios.
[0032] In various embodiments, the catalyst compositions of the disclosure have little to no crystalline Al 2 O 3 For example, in various embodiments, the crystallized Al 2 O 3 The amount of the phase is no greater than 5 wt %, such as no greater than 4 wt %, or no greater than 3 wt %, or no greater than 2 wt % or no greater than 1 wt %. In various embodiments, the catalyst composition comprises Al in an amount ranging from 1-6 wt %, or 1-4 wt %, or 1-3 wt % or 1-2 wt %. 2 O 3 In various embodiments, the catalyst composition does not contain any substantial amount of crystalline Al 2 O 3 phase, for example, not greater than 0.5 wt %.
[0033] The inventor of the present application points out that various promoters may also be present.For example, in various embodiments, the composition also includes one or more promoters, for example, calculated as the most stable oxide, and exists in a total amount of up to 20 wt %.For example, in various embodiments, one or more promoters are with 0.1-20 wt %, for example, 0.1-15 wt %, or 0.1-10 wt %, or 0.1-5 wt %, or 1-20 wt %, or 1-15 wt %, or 1-10 wt %, or 1-5 wt %, or 5-20 wt %, or 5-15 wt %, or 5-10 wt %, or 10-20 wt % or 10-15 wt % in an amount in the range.In some embodiments of the present disclosure, the catalyst composition does not include one or more promoters exceeding 15 wt % (for example, exceeding 10 wt %).
[0034] The inventors of the present application have found that the activity of the catalyst can be improved with the addition of metals such as Co, V and Fe. Without intending to be bound by theory, the inventors indicate that these metals can form solid solutions with Zn-Al spinel. Therefore, in various embodiments described herein, the catalyst composition includes one or more promoters selected from Co, V and Fe.
[0035] In some embodiments, the one or more promoters include Co. For example, in some embodiments, as Co 2 O 3Calculated, Co is present in an amount of 0.1-20 wt %. In various embodiments, the Co in the composition is present in an amount of 0.1-15 wt %, or 0.1-10 wt %, or 0.1-5 wt %, or 1-20 wt %, or 1-15 wt %, or 1-10 wt %, or 1-5 wt %, or 5-20 wt %, or 5-15 wt %, or 5-10 wt %, or 10-20 wt % or 10-15 wt %. In some embodiments, the catalyst composition does not include more than 15 wt % (e.g., more than 10 wt %) Co.
[0036] In some embodiments, one or more promoters include V. For example, in some embodiments, as V 2 O 3 Calculated, V is present in an amount of 0.1-20 % by weight. In various embodiments, the V in the composition is present in an amount of 0.1-15 % by weight, or 0.1-10 % by weight, or 0.1-5 % by weight, or 1-20 % by weight, or 1-15 % by weight, or 1-10 % by weight, or 1-5 % by weight, or 5-20 % by weight, or 5-15 % by weight, or 5-10 % by weight, or 10-20 % by weight or 10-15 % by weight. In some embodiments, the catalyst composition does not include more than 15 % by weight (e.g., more than 10 % by weight) of V.
[0037] In some embodiments, the one or more promoters include Fe. For example, in some embodiments, as Fe 2 O 3 Calculated, Fe is present in an amount of 0.1-20 wt %. In various embodiments, the Fe in the composition is present in an amount of 0.1-15 wt %, or 0.1-10 wt %, or 0.1-5 wt %, or 1-20 wt %, or 1-15 wt %, or 1-10 wt %, or 1-5 wt %, or 5-20 wt %, or 5-15 wt %, or 5-10 wt %, or 10-20 wt % or 10-15 wt %. In some embodiments, the catalyst composition does not include more than 15 wt % (e.g., more than 10 wt %) Fe.
[0038] The inventor of the present application has pointed out that various other promoters can be useful.For example, in various embodiments, one or more promoters include Cu, for example, calculated as CuO, and are present in the composition in an amount in the range of 0.1-20 wt %.In various embodiments, calculated as CuO, Cu is present in the composition in an amount in the range of 0.1-15 wt %, or 0.1-10 wt %, or 0.1-5 wt %, or 1-20 wt %, or 1-15 wt %, or 1-10 wt %, or 1-5 wt %, or 5-20 wt %, or 5-15 wt %, or 5-10 wt %, or 10-20 wt % or 10-15 wt %.In some embodiments, the catalyst composition does not include more than 15 wt % (for example, more than 10 wt %) Cu.
[0039] And in various embodiments, one or more promoters include one or more of K, Cs and Mg. For example, in various embodiments, one or more promoters include K, Cs and Mg, for example, as oxides, calculated, present in the composition in an amount in the range of 0.1-20 wt %. In various embodiments, as oxides, calculated, K, Cs and Mg are present in the composition in an amount in the range of 0.1-15 wt %, or 0.1-10 wt %, or 0.1-5 wt %, or 1-20 wt %, or 1-15 wt %, or 1-10 wt %, or 1-5 wt %, or 5-20 wt %, or 5-15 wt %, or 5-10 wt %, or 10-20 wt % or 10-15 wt %. In some embodiments, the catalyst composition does not include more than 15 wt % (for example, more than 10 wt %) of K, Cs and / or Mg.
[0040] As described above, chromium is conventionally used to provide water-gas shift catalysts with excellent activity, selectivity, and stability at elevated temperatures. However, chromium is toxic and carcinogenic, and it is therefore desirable to avoid its use wherever possible. The inventors of the present invention have discovered that the catalysts of the present disclosure exhibit good activity and stability at elevated temperatures even in the absence of chromium. Thus, in various embodiments described herein, Cr is used as a 2 O 3 The catalyst composition does not contain any substantial amount of chromium. 2 O 3 The catalyst composition does not contain more than 1 wt % chromium, calculated as Cr 2 O 3 The catalyst composition does not contain more than 0.5 wt. %, or more than 0.1 wt. %, or more than 0.01 wt. % chromium, calculated.
[0041] The catalyst compositions described herein can consist essentially of oxides of aluminum and zinc. For example, in various embodiments of the catalyst compositions otherwise described herein, Al (as Al 2 O 3 calculated) and Zn (calculated as ZnO), Co (calculated as Co 2 O 3 Calculated), V (as V 2 O 3 Calculated) and Fe (as Fe 2 O 3 The total amount of oxides of Al (calculated as Al) is at least 90 wt %, e.g., at least 95 wt %, of the catalyst composition. In other embodiments of the catalyst compositions described herein, Al (calculated as Al 2 O 3 calculated) and Zn (calculated as ZnO), Cu (calculated as CuO), Co (calculated as Co 2 O 3 Calculated), V (as V 2 O 3 Calculated) and Fe (as Fe 2 O 3 The total amount of oxides (calculated) is at least 90 wt %, for example, at least 95 wt %, of the catalyst composition.
[0042] The inventors of the present application have discovered that coprecipitation techniques can be used to prepare the zinc and aluminum mixed oxide catalysts of the present disclosure. Other techniques such as impregnation can optionally be used to add additional materials, for example, those that are not easily coprecipitated. Another aspect of the present disclosure is a method for preparing a high temperature water gas shift catalyst composition. The method includes providing an aqueous precursor solution comprising zinc ions and copper ions; precipitating a solid catalyst precursor comprising a salt of zinc, aluminum and, if present, promoter ions from the aqueous precursor solution, and then calcining the solid catalyst precursor to provide a catalyst composition.
[0043] As described above, the method includes providing a precursor solution comprising zinc ions and aluminum ions. In various embodiments described herein, providing the precursor aqueous solution includes dissolving one or more salts containing zinc ions and aluminum ions in an aqueous medium. For example, in various embodiments described herein, the one or more salts can be selected from zinc nitrate, zinc sulfate, zinc carbonate, zinc acetate, zinc chloride, zinc bromide, zinc iodide, aluminum nitrate, aluminum sulfate, aluminum carbonate, aluminum acetate, aluminum chloride, aluminum bromide and aluminum iodide. In various embodiments of the present disclosure, the one or more salts containing zinc ions and aluminum ions have the same counter ions. In other embodiments described herein, the one or more salts containing zinc ions and aluminum ions have different counter ions. In specific embodiments of the disclosure described herein, providing the precursor solution includes dissolving zinc nitrate (Zn(NO3 ) 2 ) and aluminum nitrate (Al(NO 3 ) 2 ) dissolved in aqueous medium.
[0044] As discussed above, the inventors of the present application have found that various promoters can be used to improve the activity of the catalyst. Therefore, in various embodiments, the method includes providing a precursor aqueous solution further comprising one or more promoter ions. For example, in some embodiments of the present disclosure, one or more promoter ions are selected from cobalt ions, vanadium ions, iron ions or copper ions. In various embodiments described herein, providing a precursor aqueous solution includes dissolving one or more promoter salts containing cobalt ions, vanadium ions, iron ions and copper ions in an aqueous medium. For example, in various embodiments described herein, one or more salts can be selected from cobalt nitrate, cobalt sulfate, cobalt carbonate, cobalt acetate, cobalt chloride, cobalt bromide, cobalt iodide, vanadium nitrate, vanadium sulfate, vanadium carbonate, vanadium acetate, vanadium chloride, vanadium bromide, vanadium iodide, iron nitrate, iron sulfate, iron carbonate, iron acetate, iron chloride, iron bromide, iron iodide, copper nitrate, copper sulfate, copper carbonate, copper acetate, copper chloride, copper bromide and copper iodide, and in various embodiments of the present disclosure, one or more salts containing cobalt ions, vanadium ions, iron ions and copper ions have the same counter ions. In other embodiments described herein, one or more salts containing cobalt ions, vanadium ions, iron ions, and copper ions have different counter ions. In certain embodiments of the disclosure described herein, providing a precursor solution comprises dissolving one or more promoter ion nitrates in an aqueous medium. For example, in various embodiments, providing a precursor solution comprises dissolving Co(NO 3 ) 2 , VO(NO 3 ) 3 , Fe(NO 3 ) 3 and Cu(NO 3 ) 3 One or more of the compounds are dissolved in an aqueous medium.
[0045] As described above, the method includes precipitating a solid catalyst precursor from a solution. Precipitation can be achieved by making the pH of the solution reach a range of 5 to 7.5. For example, in various embodiments of the method described in addition herein, the pH of the precursor solution is reached, for example, 5-7.2, or 5-7, or 5-6.8, or 5-6.5, or 5-6.2, or 5-6, or 5.5-7.5, or 5.5-7.2, or 5.5-7, or 5.5-6.8, or 5.5-6.5, or 6-7.5, or 6-7.2, or 6-7, or 6.5-7.5, or 6.5-7.2. Such a pH range can be maintained desirably during the entire precipitation period.
[0046] In some embodiments of the methods described herein, the precipitation step comprises adding an alkaline solution comprising carbonate ions and hydroxide ions to the precursor aqueous solution. In some embodiments of the methods described herein, the alkaline solution comprises sodium carbonate (e.g., 15-35% by weight, or 20-30% by weight) and sodium hydroxide (e.g., 5-15% by weight). Of course, other alkaline solutions may be used, for example, potassium carbonate and / or potassium hydroxide may be used instead of their sodium analogs.
[0047] In various embodiments of the methods described herein, the temperature of the precursor solution is maintained at 30° C. to 100° C. throughout the precipitation. For example, in various embodiments of the methods described herein, the temperature of the precursor solution is maintained in the range of 30-100° C., for example, 30-90° C., or 30-80° C., or 40-100° C., or 40-90° C., or 40-80° C., or 50-100° C., or 50-90° C., or 50-80° C. throughout the precipitation.
[0048] Those of ordinary skill in the art may select the time course required for precipitation. In various embodiments of the method described in addition herein, precipitation is continued in the range of 0.5-2 hours, for example, in the range of 0.5-1.5 hours, or 0.5 to 1 hour, or 1-2 hours, or 1-1.5 hours, or 1.5-2 hours. For example, in a specific embodiment, precipitation takes 1 hour. But other times can be used.
[0049] In some embodiments of the method described herein, the method further includes separating and washing the solid catalyst precursor before calcining the solid catalyst precursor. Conventional methods can be used without specific restrictions. Separation can be carried out by any desired method (e.g., filtration or centrifugation) for separating the solid precipitate from the liquid solution. Washing can be carried out by rinsing with deionized water.
[0050] As described above, the method includes calcining the solid catalyst precursor. In some embodiments of the method described in addition herein, the method further includes aging (aging) before calcining the solid catalyst precursor, washing, and then drying the solid catalyst precursor. In some embodiments of the method described in addition herein, before calcining, the solid catalyst precursor is aged after, for example, separation but before drying. In some embodiments of the method described in addition herein, the aging solid catalyst precursor lasts in the range of 5 minutes to 1 hour, for example, 5 minutes to 45 minutes, or 5 minutes to 30 minutes, or 5 minutes to 15 minutes, or 15 minutes to 1 hour, or 15 minutes to 45 minutes, or 15 minutes to 30 minutes, or 30 minutes to 1 hour, or 30 minutes to 45 minutes, or 45 minutes to 1 hour.
[0051] In some embodiments of the methods described herein, the solid catalyst precursor is dried prior to calcination. Here, conventional methods may also be used without specific limitations. In some embodiments of the methods described herein, the solid catalyst precursor is dried at a temperature in the range of 40°C to 200°C for a period of time in the range of 15 minutes to 36 hours. However, it will be appreciated by those of ordinary skill in the art that other conditions may be used (e.g., drying the material under ambient conditions), and that a separate drying step may not be necessary for some samples because water will be removed during the initial stages of heating for calcination.
[0052] The material is calcined via treatment with oxygen (typically in air) at high temperature to substantially convert the zinc and aluminum salts of the precipitate into oxides. In various embodiments of the methods otherwise described herein, the temperature of calcination is in the range of 200-1200°C. For example, in various embodiments of the methods otherwise described herein, the temperature of calcination is 300-1200°C, for example, 300-1150°C, or 300-1100°C, or 300-1050°C, or 300-1000°C, or 350-1200°C, or 350-1150°C, or 350-1100°C, or 350-1050°C, or 350-1000°C or 400-1200°C, or 400-1200°C. 00-1150°C, or 400-1100°C, or 400-1050°C, or 400-1000°C, or 450-1200°C, or 450-1150°C, or 450-1100°C, or 450-1050°C, or 450-1000°C, or 500-1200°C, or 500-1150°C, or 500-1100°C, or 500-1050°C, or 500-1000°C.
[0053] One of ordinary skill in the art will select a calcination time sufficient to substantially convert the precipitated salt into the oxide as described above. In some embodiments of the methods otherwise described herein, the solid catalyst precursor is calcined for a period of time in the range of 5 minutes to 24 hours. For example, in various embodiments of the methods otherwise described herein, the solid catalyst precursor is calcined for a period of time in the range of 5 minutes to 12 hours, or 5 minutes to 8 hours, or 1 hour to 24 hours, or 1-12 hours, or 1-8 hours, or 2-24 hours, or 2-12 hours, or 2-8 hours.
[0054] As noted above with respect to various aspects and embodiments of the catalyst compositions of the present disclosure, metal sources other than Zn and Al (e.g., Co, V, Fe or Cu sources) can be, for example, carbonates, nitrates, acetates, formates, oxalates, molybdates, or citrates, or any compound that provides such a promoter metal to the calcined catalyst composition. Some of these substances can be precipitated with zinc and aluminum salts. In other embodiments of the methods described herein, the method further includes providing one or more of cobalt, vanadium, iron and copper to the composition by an impregnation step. In various embodiments of the methods described herein, the method includes impregnating the calcined composition by incipient wetness impregnation.
[0055] In various embodiments of the methods described herein, the calcining step occurs before the impregnation step. In various embodiments of the methods described herein, the calcining step occurs after the impregnation step. In various embodiments of the methods described herein, the calcining step occurs both before and after the impregnation step. Post-impregnation drying and calcining can be carried out, for example, at the temperature and time ranges disclosed above for calcination of the precipitate.
[0056] Although specific methods are described here, the inventors of the present application also point out that catalysts with spinel structures can be prepared by various conventional routes. For example, catalysts can be prepared by conventional precipitation routes that produce layered double hydroxides or oxy-hydroxide structures. Heat treatment of the precipitate produces a spinel structure. Different preparation methods (such as coprecipitation, acid / base addition, urea uniform coprecipitation, Pechini method and citric acid complexation) can be applied to catalyst synthesis. Zinc, magnesium, aluminum, copper, cobalt, vanadium, iron, manganese, cerium and other divalent and trivalent metal salts can be used in the synthesis of catalysts and can be provided by coprecipitation or by impregnation.
[0057] Another aspect of the disclosure is a catalyst composition prepared by the methods described herein. Advantageously, the inventors have determined that the use of such a catalyst composition can catalyze the high temperature water-gas shift reaction with comparable efficiency to conventional chromium-containing catalyst materials, and in certain embodiments can operate over a wider range of steam to gas ratios than conventional catalyst materials.
[0058] The compositions described herein are particularly useful for water-gas shift reactions, for example, in water-gas shift reactions carried out at relatively high temperatures. As will be appreciated by those of ordinary skill in the art, the water-gas shift reaction converts water and carbon monoxide into hydrogen and carbon dioxide. Therefore, another aspect of the present disclosure is a method for carrying out a water-gas shift reaction, comprising contacting a feed comprising water and carbon monoxide with a catalyst composition described herein under certain conditions to cause the formation of hydrogen and carbon dioxide. The feed may be formed, for example, by gasification of an organic feedstock such as coal or biomass.
[0059] In some embodiments of the water-gas shift process otherwise described herein, the feed comprises water and gas (i.e., comprises carbon monoxide) in a steam to gas (S / G) molar ratio of at most 1. For example, in certain such embodiments, the S / G ratio of the feed is at most 0.8, or at most 0.6, or at most 0.5, or at most 0.4, or at most 0.3, or in the range of 0.2 to 1, or 0.4 to 1, or 0.5 to 1, or 0.6 to 1, or 0.7 to 1, or 0.1 to 0.6, or 0.2 to 0.7, or 0.3 to 0.8, or 0.4 to 0.9.
[0060] In some such embodiments of the hydrogen formation method described in addition herein, the feed comprises carbon monoxide in an amount in the range of 5 wt % to 25 wt %. For example, in some embodiments of the hydrogen formation method described in addition herein, the feed comprises carbon monoxide in an amount in the range of 5 wt % to 20 wt %, or 5 wt % to 15 wt %, or 10 wt % to 25 wt %, or 15 wt % to 25 wt %, or 10 wt % to 20 wt % or 10 wt % to 15 wt %. In some embodiments of the hydrogen formation method described in addition herein, the feed comprises hydrogen. In some embodiments of the hydrogen formation method described in addition herein, the feed comprises carbon dioxide and / or nitrogen.
[0061] The contact of the feed with the catalyst composition described herein can be carried out in various ways familiar to those of ordinary skill in the art. Conventional equipment and methods can be used together with the catalyst composition of the present disclosure to provide beneficial performance. Therefore, the catalyst can be contained in a bed in a reactor vessel or divided into multiple beds in a reactor. The reaction system can contain one or more reaction vessels in series. The feed to the reaction zone can flow vertically upward in a typical plug flow reactor, or flow downward through the catalyst bed, or flow horizontally through the catalyst bed in a radial flow reactor.
[0062] The catalyst compositions described herein are desirably in a substantially reduced form. Thus, it may be desirable to treat the catalyst composition with hydrogen, for example, prior to contacting the catalyst composition with the feed. Such treatment may be performed as follows: at a temperature in the range of, for example, 250° C. to 400° C., at a temperature of, for example, 10,000 h. -1 Up to 30000 h -1 In the range (e.g. 12000 h -1 Up to 24000 h -1 The method is preferably carried out in flowing hydrogen at a GHSV in the range of 2 bar to 16 bar, for a period of at least 4 hours, for example, for a period in the range of 8 hours to 24 hours.
[0063] The contacting of the feed with the catalyst composition can be carried out using conventional methods. For example, the feed can be introduced into a reaction zone containing the catalyst composition at a constant rate, or alternatively, at a variable rate. The hydrogen formation can be carried out under gas phase conditions.
[0064] In some embodiments of the hydrogen formation methods otherwise described herein, at 10000 h -1 Up to 30000 h -1 The feed is contacted with a provided catalyst composition at a gas hourly space velocity in the range of 1000 h / min to 2000 h / min. For example, in certain embodiments of the hydrogen formation methods described elsewhere herein, at 12000 h / min -1 Up to 30000 h -1 , or 14000 h -1 Up to 30000 h -1 , or 16000 h -1 Up to 30000 h -1 , or 10000 h -1 Up to 28000 h -1 , or 10000 h -1 Up to 26000 h -1 , or 10000 h -1 Up to 24000 h -1 , or 10000 to 22000 h -1 , or 10000 h -1 Up to 20000 h -1 , or 12000 h -1 Up to 28000 h -1 , or 14000 h -1 Up to 26000 h -1 , or 16 h -1 Up to 24000 h -1 or 16000 h -1 Up to 24000 h -1The feed is contacted with the provided catalyst composition at a gas hourly space velocity within the range of .
[0065] In some embodiments of the hydrogen formation methods otherwise described herein, the methods are conducted at a temperature in the range of 250° C. to 650° C. For example, in certain embodiments of the hydrogen formation methods otherwise described herein, the methods are conducted at a temperature in the range of 275° C. to 650° C., or 300° C. to 650° C., or 325° C. to 650° C., or 250° C. to 625° C., or 250° C. to 600° C., or 250° C. to 575° C., or 250° C. to 550° C., or 250° C. to 525° C., or 250° C. to 500° C., or 250° C. to 475° C., or 275° C. to 600° C., or 300° C. to 575° C., or 325° C. to 550° C., or 325° C. to 525° C., or 325° C. to 500° C.
[0066] In some embodiments of the hydrogen forming methods otherwise described herein, the method is carried out at a pressure in the range of 5 barg to 40 barg. For example, in certain embodiments of the hydrogen forming methods otherwise described herein, the method is carried out at a pressure in the range of 7.5 barg to 40 barg, or 10 barg to 40 barg, or 12.5 barg to 40 barg, or 15 barg to 40 barg, or 20 barg to 40 barg, or 25 barg to 40 barg, or 5 barg to 35 barg, or 5 barg to 30 barg, or 5 barg to 25 barg, or 5 barg to 20 barg, or 5 barg to 15 barg, or 7.5 barg to 35 barg, or 10 barg to 30 barg, or 12.5 barg to 25 barg.
[0067] For example, in certain embodiments further described herein, the water-gas shift reaction is a high temperature shift reaction, e.g., a reaction conducted at a temperature in the range of 300-450° C. In other embodiments further described herein, the water-gas shift reaction is a medium temperature shift reaction, e.g., a reaction conducted at a temperature in the range of 220-295° C. And in other embodiments further described herein, the water-gas shift reaction is a low temperature shift reaction, e.g., a reaction conducted at a temperature in the range of 180-220° C. Example
[0068] The following examples are illustrative of specific embodiments of the compositions and methods of the present disclosure and various uses thereof. They are presented for illustrative purposes only and are not to be construed as limiting the scope of the present disclosure.
[0069] Example 1: Preparation of catalyst with high Zn:Al ratio
[0070] To prepare a high temperature water-gas shift catalyst with a high Zn:Al ratio, 4.399 kg of NaAlO 2 The precursor acid solution was prepared by dissolving 61.71 kg of deionized water (28.63% Al) powder. Next, 32.464 kg of 67% HNO 3 Add to the sodium aluminate solution and mix vigorously. Once well mixed, add 5.753 kg of ZnO (80.26% Zn) to the aluminum nitrate solution and mix until completely dissolved. Then, add 1.998 kg of Cu(NO 3 ) 2 (14.95% Cu) solution is added to Zn / Al solution and dissolved.Then the acid solution is pumped to still #1 and flushed with 15 kg of deionized water.Repeat this whole process to prepare two batches of acid solution and add extra 39 kg of deionized water to the acid still to target 226 liters (264 kg).The target acid still weight is 267 kg, and the actual weight is 264 kg.By adding 21.27 kg of Na 2 CO 3 The powder was dissolved in 80.82 kg of deionized water to prepare the alkali solution. Then 4.254 kg of 50% NaOH solution was added to the dissolved sodium carbonate solution. This whole process was repeated to prepare two batches of alkali solution. The target alkali kettle weight was 213 kg, while the actual weight was 214 kg.
[0071] The precursor acid and base solutions were pumped into a kettle containing 159 kg of deionized water heated to 60°C. The solutions were mixed in the container to cause a precipitate to form. The solution was pumped for approximately 1 hour and the pH of the solution was 7 during precipitation. Since this was two batches, the coprecipitation process was repeated. Once all the precursor acid solutions were added for each batch, the stirred suspension was heated to 60°C for 30 minutes. After 30 minutes of aging, the suspension was filtered using a Shriver filter press and washed with deionized water to make the filtrate conductivity less than 200 μS. The Mg(CH 3 COO 2 and K(CH 3 The final filter cake was reslurried with an aqueous solution of 2,4-dichloro-2-(2-oxo-4-oxo-2-yl)-4-nitro-2-ol (COO). The impregnated slurry was spray dried and then calcined at 450°C for 2 hours. The calcined powder was mixed with graphite, tableted and the tablets were calcined at 600°C to provide Catalyst E1.
[0072] Two comparative catalysts were also prepared. To prepare these catalysts, 74.2 g of NaAlO 2The precursor acid solution was prepared by dissolving (28.5% Al) powder in 500 mL of deionized water. The solution was then mixed with 461.8 g of 58% HNO 3 Next, 31.73 g of ZnO (80.35% Zn) powder was dissolved in the solution. Once the ZnO was completely dissolved, 9.69 g of Cu(NO 3 ) 2 (27.22% Cu) crystals were added to the solution and dissolved. Finally, 185 g of deionized water was added to dilute the total solution volume to 1 L. The 10% NaOH solution was diluted to 1 L by mixing 240 g of 10% NaOH solution and 960 g of 25% NaOH. 2 CO 3 This produces approximately 1 L of base solution.
[0073] The precursor acid and base solutions were pumped into a jacketed vessel containing deionized water heated to 60°C. The solutions were mixed in the vessel, causing a precipitate to form. The solution was pumped for approximately 1 hour and the pH of the solution was 7 during precipitation. Once all the precursor acid solution was added, the stirred suspension was heated to 60°C for 30 minutes. After 30 minutes of aging, the suspension was filtered and washed with deionized water to make the filtrate conductivity less than 200 μS. The final filter cake was then dried at 120°C. The dried filter cake was ground into a powder and precipitated with Mg(CH 3 COO 2 and K(CH 3 The impregnated powder was dried at 120°C and then calcined at 450°C for 2 hours. The calcined powder was mixed with graphite, sheeted and the sheet was calcined at 600°C to provide comparative catalyst C1.
[0074] A second comparative catalyst was prepared by mixing 73.2 g of NaAlO 2 The precursor acid solution was prepared by dissolving (28.9% Al) powder in 500 mL of deionized water. The solution was then mixed with 453.3 g of 58% HNO 3 Next, 31.73 g of ZnO (80.35% Zn) powder was dissolved in the solution. Once the ZnO was completely dissolved, 9.78 g of Cu(NO 3 ) 2 (26.96% Cu) crystals were added to the solution and dissolved. Finally, 208 g of deionized water was added to dilute the total solution volume to 1 L. The solution was prepared by mixing 240 g of 10% NaOH solution and 960 g of 25% Na 2 CO 3 This produces approximately 1 L of base solution.
[0075] The precursor acid and base solutions were pumped into a jacketed vessel containing deionized water heated to 60°C. The solutions were mixed in the vessel, causing a precipitate to form. The solution was pumped for approximately 1 hour and the pH of the solution was 7 during precipitation. Once all the precursor acid solution was added, the stirred suspension was heated to 60°C for 30 minutes. After 30 minutes of aging, the suspension was filtered and washed with deionized water to make the filtrate conductivity less than 200 μS. The final filter cake was then dried at 120°C. The dried filter cake was ground into a powder and precipitated with Mg(CH 3 COO 2 and K(CH 3 The impregnated powder was dried at 120°C and then calcined at 450°C for 2 hours. The calcined powder was mixed with graphite, sheeted and the sheet was calcined at 600°C to provide comparative catalyst C2.
[0076] Catalysts E1, C1 and C2 were analyzed by XRD to determine their compositions, the results of which are reported in Table 1.
[0077] Table 1. Catalyst composition
[0078] Example 2: Performance of high Zn:Al ratio catalysts
[0079] All examples were first reduced with feed gas at 330°C at 3.4 barg for 16 h and tested in a fixed bed test apparatus under typical high temperature water gas shift conditions. -1 At a dry gas hourly space velocity (GHSV) of 0.6, an S / G ratio of 0.6 and a total pressure of 29 barg, a 23.2% N 2 , 12.8% CO, 7.8% CO 2 A simulated feed of 15 ppm H2 was introduced into the feed gas to determine the sulfur tolerance of the catalyst. 2 The bed temperature was gradually increased from 330°C to 371°C. The CO concentration at the reactor outlet was monitored by an online gas chromatograph (GC). The average CO conversion of each test at 330°C and 371°C is listed in Table 2.
[0080] Table 2. Performance of high Zn:Al ratio catalysts
[0081] Example 3: Preparation and performance of catalysts containing V and Fe promoters
[0082] A series of X-ray powder diffraction experiments were performed on the spent catalysts to probe the structure of the active species responsible for the enhanced activity.
[0083] Three materials without promoter were prepared by coprecipitation with Zn / Al = 1, 1.25 and 1.5 (E2, E3, E4). The powders were calcined at 1000 °C. The structures were analyzed by XRD before use in the reactor. All three samples contained ZnAl 2 O 4 Spinel and ZnO. The relative amounts of the two phases vary with the Zn / Al ratio in the formulation (Table 3). Since Zn is in excess in all three samples, the unit cell size and the composition of the spinel do not change.
[0084] Table 3. Catalyst composition
[0085] Catalysts containing vanadium and iron promoters were also prepared and then tested for their high temperature water gas shift performance. The spent vanadium promoter catalysts (E5 and E6) and the spent iron promoter catalysts (E7, E8 and E9) were analyzed by XRD to determine their compositions, the results of which are reported in Table 4. A comparative catalyst (C3) with a large amount of iron was also prepared and analyzed.
[0086] Table 4. Catalyst composition with promoter
[0087] Figure 1 XRD patterns of the unpromoted (E4) and V-promoted (E5 and E6) spent catalysts are shown. All three samples contain broad peaks associated with the spinel structure. The unit cell size of the spinel phase in the unpromoted sample (E4) matches that of ZnAl quite closely. 2 O 4 The literature value (a=8.0869 Å). As the V content increases, the spinel unit cell size of the V-promoted sample increases significantly (Table 4). 3+ and V 3+ The phenomenon can be explained by the different ionic radii of the metals in the crystal. Table 5 lists the ionic radii of various metals with different coordination numbers in the crystal. 3+ Replace AB 2 O 4 Al in the octahedral B lattice of the spinel structure 3+ When , the unit cell expansion occurs and the corresponding peak moves to a lower angle. The high temperature water gas shift test results show that at 371 ° C and S / G = 0.6, the V-promoted sample has a higher CO conversion than the unpromoted catalyst, and the activity improvement is more significant with higher vanadium content.
[0088] Table 5. Ionic radii of metals in crystals
[0089] Similar phenomena were observed in Fe-promoted catalysts (E7, E8, E9). Figure 2 XRD patterns of unpromoted (E4) and Fe promoted (E7, E8, E9) spent catalysts are shown. The unit cell size of the spinel phase increases with higher Fe levels in the formulation (Table 4), indicating that Fe is incorporated into the ZnAl spinel phase ( Figure 2 ).
[0090] A catalyst with a very high Fe level of 34.4% Fe was prepared (C3). C3 also contained a cubic spinel phase with a large unit cell size after the high temperature water gas shift reaction (Table 4). This phase is best replaced by aluminum-substituted zinc iron oxide (ZnFe 1.5 Al 0.5 O 4 , 04-007-6615). Sample C3 also contains trace amounts of hematite. Test results show that at 371°C and S / G=0.6, those samples with high Fe levels have lower CO conversion and much higher methane production than samples containing less than 10% Fe.
[0091] The details shown herein are presented as examples only and for the purpose of illustrative discussion of preferred embodiments of the invention, and are presented for the purpose of providing what is believed to be the most useful and easy-to-understand description of aspects of the principles and concepts of various embodiments of the invention. In this regard, no attempt is made to show the structural details of the invention in more detail than is necessary for a basic understanding of the invention, and the description in conjunction with the accompanying drawings and / or examples makes it clear to those skilled in the art how several forms of the invention are embodied in practice. Therefore, before describing the disclosed methods and apparatus, it should be understood that the aspects described herein are not limited to specific embodiments, instruments or configurations, and therefore can certainly be changed. It should also be understood that the terms used herein are only for the purpose of describing specific aspects, and are not intended to be limiting unless expressly defined herein.
[0092] The terms "a", "an", "the" and similar references used in the context of describing the present invention (especially in the context of the claims below) should be construed to cover both the singular and the plural, unless otherwise indicated herein or clearly contradicted by context. Recitation of ranges of values herein is merely intended to serve as a shorthand method of referring individually to each individual value falling within the range. Unless otherwise indicated herein, each individual value is incorporated into the specification as if it were individually recited herein. It will be further understood that the endpoints of each range are significant not only in relation to the other endpoints, but also independently of the other endpoints.
[0093] All methods described herein can be performed in the order of any suitable steps, unless otherwise indicated herein or clearly contradictory to the context. The use of any and all embodiments provided herein, or exemplary language (e.g., "such as") is intended only to better illustrate the present invention and does not set limitations on the scope of the present invention otherwise claimed. No language in the specification should be interpreted as indicating any unclaimed elements essential to the practice of the present invention.
[0094] Unless the context clearly requires otherwise, throughout the specification and claims, the words 'comprise,' 'comprising,' and the like are to be interpreted in an inclusive sense, as opposed to an exclusive or exhaustive sense; that is, in the sense of "including, but not limited to." Words using the singular or plural also include the plural and singular, respectively. Additionally, when the words "herein," "above," and "below," and words of similar meanings are used in this application, they shall refer to this application as a whole and not to any particular portion of this application.
[0095] As will be understood by one of ordinary skill in the art, each embodiment disclosed herein may comprise, consist essentially of, or consist of the specifically identified elements, steps, ingredients, or components thereof. As used herein, the transitional terms "comprise" or "comprises" are meant to include, but are not limited to, and permit the inclusion of unspecified elements, steps, ingredients, or components, even in large quantities. The transitional phrase "consisting of" excludes any unspecified elements, steps, ingredients, or components. The transitional phrase "consisting essentially of" limits the scope of the embodiment to the identified elements, steps, ingredients, or components and those that do not materially affect the embodiment.
[0096] Unless indicated to the contrary, the numerical parameters set forth in the specification and attached claims are approximations that may vary depending upon the desired properties sought to be obtained by the present invention. At the very least, and not as an attempt to limit the application of the doctrine of equivalents to the scope of the claims, each numerical parameter should at least be construed in light of the number of reported significant digits and by applying ordinary rounding techniques.
[0097] Notwithstanding that the numerical ranges and parameters setting forth the broad scope of the invention are approximations, the numerical values set forth in the specific examples are reported as precisely as possible. Any numerical value, however, inherently contains certain errors resulting from the standard deviation found in their respective testing measurements.
[0098] The grouping of the optional elements or embodiments of the invention disclosed herein should not be construed as limiting. Each group member may be referred to and claimed individually or in any combination with other members of the group or other elements present herein. It is expected that one or more members of the group may be included in the group, or deleted from the group, due to convenience and / or patentable reasons. When any such inclusion or deletion occurs, it is considered that the specification contains the modified group, and therefore satisfies the written description of all Markush groups used in the appended claims.
[0099] Some embodiments of the present invention are described herein, including the best mode known to the inventor for carrying out the present invention. Of course, for those skilled in the art, when reading the foregoing description, variations of the embodiments described will become clear. The inventor expects that a skilled person will adopt such variations as appropriate, and the inventor intends to practice the present invention in a manner other than the specific description herein. Therefore, the present invention includes all modifications and equivalents of the subject matter recorded in the appended claims as allowed by applicable law. In addition, the present invention includes any combination of the elements described above in all possible variants thereof, unless otherwise indicated herein or clearly contradictory to the context.
[0100] Throughout this specification, a number of patents and printed publications are cited. Each of the cited references and printed publications is incorporated herein by reference in its entirety.
[0101] In addition, it should be understood that the embodiments of the invention disclosed herein are illustrative of the principles of the present invention. Other modifications that may be adopted are within the scope of the present invention. Therefore, by way of example, but not as a limitation, alternative configurations of the present invention may be used consistent with the teachings herein. Therefore, the present invention is not limited to what is precisely shown and described.
Claims
1. A high temperature water-gas shift catalyst composition comprising: a zinc-aluminum spinel phase, present in the composition in an amount of 30-95% by weight; and A ZnO phase, present in the composition in an amount of 5-70 wt %; The molar ratio of Zn atoms to Al atoms in the catalyst composition is at least 1:
1.
2. The catalyst composition of claim 1, wherein the zinc-aluminum spinel phase has an average crystallite size in the range of 1-100 nm (e.g., 1-75 nm, or 1-50 nm, or 1-30 nm, or 5-100 nm, or 5-75 nm, or 5-50 nm, or 5-30 nm, or 10-100 nm, or 10-75 nm, or 10-50 nm, or 25-100 nm, or 25-75 nm or 50-100 nm).
3. The catalyst composition according to claim 1, further comprising one or more promoters, for example, present in a total amount of up to 20% by weight calculated as the most stable oxide.
4. The catalyst composition of claim 3, wherein the one or more promoters comprises Co, for example, present in the composition in an amount of 0.1-20 wt %, calculated as Co2O3.
5. The catalyst composition of claim 3, wherein the one or more promoters comprise V, for example, present in the composition in an amount of 0.1-20 wt. %, calculated as V2O3.
6. The catalyst composition of claim 3, wherein the one or more promoters include Fe, for example, calculated as Fe2O3, present in the composition in an amount of 0.1-20 wt%.
7. A method for preparing the high temperature water-gas shift catalyst composition according to claim 1, the method comprising: providing a precursor aqueous solution comprising zinc ions and aluminum ions; precipitating a solid catalyst precursor comprising salts of zinc, aluminum and, if present, promoter ions from an aqueous precursor solution; and then The solid catalyst precursor is calcined to provide a catalyst composition.
8. The method of claim 7, wherein providing a precursor solution comprises dissolving Zn(NO3)2 and Al(NO3)3 in an aqueous medium.
9. The method of claim 7, wherein precipitating the solid catalyst precursor comprises bringing the pH of the solution to a range of 5-7.5 (eg, 6.5-7.2).
10. (This modification) The method according to claim 7, wherein the temperature of the precursor solution is maintained at 30°C to 100°C (e.g., 50°C to 80°C) throughout the precipitation period.
11. The catalyst composition according to claim 1, which is prepared by the method according to claim 7.
12. A method of performing a water gas shift reaction, the method comprising contacting a feed comprising water and carbon monoxide with a catalyst composition according to claim 1 to form hydrogen and carbon dioxide.
13. A process according to claim 12, wherein the steam to gas ratio of the feed is at most 1.
14. The method of claim 12, wherein the feed is contacted with the catalyst composition at a temperature in the range of 250°C to 650°C (eg, 300°C to 600°C).
15. The process of claim 12, wherein the feed is contacted with the catalyst composition at a pressure in the range of 5 barg to 40 barg.
